Factors Related to Behavioral Beautiful Behavior in Sambimaya Village Juntinyuat Indramayu in 2019 - Royani Jahidin; Sutangi; Tating Nuraeni (Penerbit Hellow Pustaka, 2025)
Background : The problem of sanitation development in Indonesia is a matter of socio-cultural challanges, one of which is the behavior of residents who are accustomed to defecating in the open place. These habits will automatically become a source of disease transmission if not taken seriously. Sambimaya Village is a village with limited access to the use of latrine, this is influenced by various factors such as the level of knowledge, education, latrine ownership and economy. Research Method : Using analytic observation design with Cross Sectional approach. The population of this research is all family heads in Sambimaya Village Juntinyuat District Indramayu Regency in 2019 as many as 1.024 families. The number of samples was 92 households taken systematically random sampling. Data were statistically analyzed using the Chi Square Test with a confidence level of 95%. Research Results : From the statistical test knowledge ρ value 0,000 < α (0,05), education ρ value 0,052 > α (0,05), latrine ownership ρ value 0,000 < α (0,05), and economic ρ value 0,919 > α (0,05). Research Conclusions : There is no relationship between education and economics with open defecation behavior in Sambimaya Village Juntinyuat Indramayu District in 2019.